Poly (ADP-Ribose) polymerase 1 and parthanatos in neurological diseases: From pathogenesis to therapeutic opportunities - Xiaoxue Xu; Bowen Sun; Chuansheng Zhao (Neurobiology of Disease, 2023)
Poly (ADP-ribose) polymerase-1 (PARP-1) is the most extensively studied member of the PARP superfamily, with its primary function being the facilitation of DNA damage repair processes. Parthanatos is a type of regulated cell death cascade initiated by PARP-1 hyperactivation, which involves multiple subroutines, including the accumulation of ADP-ribose polymers (PAR), binding of PAR and apoptosis-inducing factor (AIF), release of AIF from the mitochondria, the translocation of the AIF/macrophage migration inhibitory factor (MIF) complex, and massive MIF-mediated DNA fragmentation. Over the past few decades, the role of PARP-1 in central nervous system health and disease has received increasing attention. In this review, we discuss the biological functions of PARP-1 in neural cell proliferation and differentiation, memory formation, brain ageing, and epigenetic regulation. We then elaborate on the involvement of PARP-1 and PARP-1-dependant parthanatos in various neuropathological processes, such as oxidative stress, neuroinflammation, mitochondrial dysfunction, excitotoxicity, autophagy damage, and endoplasmic reticulum (ER) stress. Additional highlight contains PARP-1's implications in the initiation, progression, and therapeutic opportunities for different neurological illnesses, including neurodegenerative diseases, stroke, autism spectrum disorder (ASD), multiple sclerosis (MS), epilepsy, and neuropathic pain (NP). Finally, emerging insights into the repurposing of PARP inhibitors for the management of neurological diseases are provided. This review aims to summarize the exciting advancements in the critical role of PARP-1 in neurological disorders, which may open new avenues for therapeutic options targeting PARP-1 or parthanatos.